PERAN WORD OF MOUTH MEMEDIASI PENGARUH CUSTOMER EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN DI PASAR SENI KABUPATEN KLUNGKUNG - Wisnu Murti Adnyana, I Gede Wasudewa; Oktora Panasea, I Gede Nandya (Buletin Studi Ekonomi; VOLUME.29.NO.02.TAHUN.2024DO - 10.24843/BSE.2024.v29.i02.p02, 2024)
The Klungkung Regency art market is one of the art markets in the province of Bali which sells endek and songket fabrics which are one of the needs of the community. The purpose of this study is to explain the role of word of mouth in mediating the effect of customer experience on purchasing decisions at the art market in Klungkung Regency. This study used a sample of 130 people and used a purposive sampling technique. Data collection in this study was carried out by survey and questionnaire methods. This study uses classical assumption test techniques, path analysis and Sobel test. Based on the results of this study, the results obtained were that customer experience had a positive and significant effect on purchasing decisions at the Klungkung regency art market, customer experience had a positive and significant effect on word of mouth at the Klungkung regency art market, word of mouth had a positive and significant effect on purchasing decisions at art market in Klungkung regency, word of mouth is a mediating variable that partially influences customer experience on purchasing decisions in the art market in Klungkung regency.